ANALISIS NUMERALIA DALAM BAHASA RAJA AMPAT DIALEK WARDO DI KAMPUNG AREFI KABUPATEN RAJA AMPAT - Soulisa, Irwan; Kabes, Audrey Sharoon Y. (LPPM Politeknik Saint Paul Sorong, 2024)
The formulation of the problem in this research is how the numeralia of the Raja Ampat language of the Wardo dialect in Arefi village, Raja Ampat district. This research aims to identify the forms of numeralia and types of numeralia in the Wardo dialect in Raja Ampat district. This research is in the form of qualitative research. The subject in this research is the researcher himself and the data source in this research comes from sources who are native speakers of the Wardo dialect. The data collection techniques in this research are free-involved listening, interview techniques, note-taking and documentation techniques. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The numeralia results obtained in this research are based on the types of numeralia, namely; definite basic numerals (20), collective basic numerals (5), distributive basic numerals (3), indefinite basic numerals (6). In this research, it can be concluded that the numeralia in the Raja Ampat language of the Wardo dialect has its own characteristics, namely when the numeralia in an Indonesian sentence is placed at the beginning of the sentence, in the Wardo dialect it will move to the middle or end of the sentence depending on the subject in the sentence